Which oral contraceptives are more effective for the treatment of adult acne in females?. Issue 2 (February 2017) - Myran, Leena; Nguyen, Thanh‐Nga
Abstract : EVIDENCE‐BASED ANSWER : Combined oral contraceptives (COCs) improve acne compared with placebo. COCs with drospirenone appear to decrease total lesion counts slightly more than COCs with norgestimate and are 84% less likely to be associated with acne deterioration than COCs with levonorgestrel. There do not appear to be differences in the comparative effectiveness in treating acne of COCs containing levonorgestrel versus norethindrone acetate and desogestrel versus norgestimate (SOR: B, systemic review of RCTs and single RCT without specific recommendation).